A National Engagement Model for Developing Computer Science Education in Wales - Faron Moller (ISSEP'2016: The 9th International Conference on Informatics in Schools, 2016)
Computer science education in the United Kingdom has undergone substantial scrutiny, and in England a new computing curriculum has just been introduced. However, in Wales - a devolved nation within the UK - political, geographical and socio-technical issues have hindered any substantive educational policy or curriculum reform for computer science over the past ten years. In this paper we present the activities of Technocamps, a university-based schools outreach programme founded in 2003 and its wider impact on computer science education and teachers in Wales. Furthermore, with imminent curriculum reform, we frame the wider opportunity for sustainably embedding both high-value digital competencies and computer science education - as well as changing the wider public perception and importance of computer science - as a prospective replicable case study of a national engagement model for countries with similar aspirations of becoming digitally confident and capable nations.